Answer:
HOOO YOU SHOULD KNO THIS!!!
Step-by-step explanation:
Answer:
Step-by-step explanation:
If DE = 4x+10,EF =2X -1, and DF= 9x - 15 find DF
(de + ef ) - df = 2e || 2e/2 = e || ed - e = d || ef - e = f || f + d = df
de + ef = 6x + 11 || (6x +11) - df = -3x -6 || 2e/2 = -3x/2 - 3 || (-3x/2 - 3) - de = x/2 + 7|| (- 3x/2 - 3) - ef = -x/2 - 1|| d + f = 6
Hey!
![-6(2x-5) = 18](https://tex.z-dn.net/?f=%20-6%282x-5%29%20%3D%2018%20)
Switch it around and it becomes:
![2x - 5 = 18 \div -6](https://tex.z-dn.net/?f=%202x%20-%205%20%3D%2018%20%5Cdiv%20-6%20)
First find 18 ÷ -6
![18 \div -6 = -3](https://tex.z-dn.net/?f=%2018%20%5Cdiv%20-6%20%3D%20-3%20)
Positive ÷ negative OR negative ÷ positive is always negative.
That leaves you with:
![2x - 5 = -3](https://tex.z-dn.net/?f=%202x%20-%205%20%3D%20-3%20)
Switch that around and it becomes:
![-3 + 5 = 2x](https://tex.z-dn.net/?f=%20-3%20%2B%205%20%3D%202x%20)
Find -3 + 5
![-3 + 5 = 2](https://tex.z-dn.net/?f=%20-3%20%2B%205%20%3D%202%20)
That leaves you with:
![2 = 2x](https://tex.z-dn.net/?f=%202%20%3D%202x%20)
Divide both sides by 2 to leave <em>x</em> alone
![\frac{2}{2} = \frac{2x}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B2%7D%20%3D%20%20%5Cfrac%7B2x%7D%7B2%7D%20%20)
![\framebox{x = 1}](https://tex.z-dn.net/?f=%20%5Cframebox%7Bx%20%3D%201%7D%20)
I believe it is 1, but i'm not completely sure.
Answer: The first one
Step-by-step explanation: